PENGARUHKESEHATAN DAN KESELAMATAN KERJA (K3) TERHADAP KINERJA KARYAWAN PADA PT. UTAMA CORE 1,2 ALBASIA DI KABUPATEN KENDAL - Eddi Indro Asmoro; Muryani Setiyastuti (Jurnal Ilmiah Dinamika Teknik, 2021)
There are issues related to the performance of employees was about a decrease in employee performance, indiscipline employees of PT. Utamacore Albisia Kendal, in addition, the occupational safety and health that was applied is not good, which results in high work accidents and high number of employees who are sick due to work. The decline in employee performance will certainly have a bad impact on the company. This study aims to determine whether occupational health and safety affect the performance of employees at PT Utamacore Alba sia Kendal. This research uses descriptive and quantitative research. The population in this study were employees totaling 100 employees. Sampling using random sampling technique as many as 50 employees. The collection method used in this study is primary data obtained from questionnaires. The data analysis method used multiple linear regression analysis with the help of the Statistical Product and Service Solution (SPSS) program. The results of this study indicate that simultaneously the variables of occupational health and safety have a significant effect on employee performance. The results of this study also show that partially the occupational health and safety variables have a significant effect on employee